PENDIDIKAN AGAMA DALAM PERSPEKTIF FILSAFAT IDEALISME - Agustinus Wisnu Dewantara (Bahasa Indonesia, 2022)
Idealism is a philosophical paradigm which views that the reality that exists in natural life is not an essential truth, but only a description of the ideas that exist in the world of ideas. Idealism is oriented to ideas, to the soul, to spirituality, to ideals, to norms that contain absolute truth. The ideal nature contains absolute, genuine, pure, and holy. This paper wants to explore how to apply the flow of idealism in the world of religious education. Why is this important? The Law on the National Education System (Undang-Undang Sisdiknas) orders that every student receive religious education according to their beliefs. Religious education is certainly an education about ideals, because it talks about God as the Supreme Ideal and encourages humans to have an ideal spiritual life. This paper is important to contribute some basic things in the perspective of idealism. Idealism assumes that knowledge is something that arises and is born from events in the human soul. The purpose of religious education in this perspective is thus to create human beings with noble personalities and have a higher and ideal standard of spiritual life and have a sense of responsibility to society.